ChemInform Abstract: Unprecedented Reaction of Ninhydrin with Ethyl Cyanoacetate and Diethyl Malonate on Ultrasonic Irradiation. Issue 20 (April 2016) - Saini, Yeshwinder; Khajuria, Rajni; Rana, Love Karan; Hundal, Geeta; Gupta, Vivek K.; Kant, Rajni; Kapoor, Kamal K.
Abstract: In addition to the title reactions, ninhydrin is also transformed with ethyl acetonate, ethyl nitroacetate, and dimedone.